TITIP AMPLOP SEBAGAI PENGGANTI MENGHADIRI UNDANGAN WALIMATUL ‘URS PERSPEKTIF HUKUM ISLAM - Syukron Choibir; Sudirwan Sudirwan (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2022)
There are many phenomena or events when someone is invited to attend the walimatul 'urs but does not attend without excuse and only leaves an envelope containing alms or donations as a substitute for attending the invitation. The purpose of this research is to find out the law on entrusting envelopes as a substitute for attending invitations from Islamic legal perspectives. The research method used is the study library method, which is a research method carried out by examining various references and results of similar previous research which is useful for obtaining a theoretical basis regarding the problem to be researched. The results of the research in this thesis are that the law of attending a walimatul 'urs invitation is mandatory if there is no 'udzur. Envelope delivery is not valid to be used as a substitute for attending a walimatul 'urs invitation. Because sunnah worship cannot replace obligatory worship. Attending a walimatul 'urs invitation has mandatory legal status if the invitation meets the requirements as an invitation that must be attended. A person who does not attend the walimah without an excuse will still incur sin. However, if you have an excuse, the legal obligation to attend the invitation will be void. The envelopes or alms he gives still have the value of worship but cannot cancel the obligation to attend the walimah.